MEMBANGUN PARADIGMA HUKUM ISLAM UNTUK PEMBAHARUAN HUKUM BISNIS SYARIAH DI INDONESIA: STUDI ANALISIS PADA KOMPILASI HUKUM EKONOMI SYARIAH - Baiduri, Baiduri (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2017)
This study aims to offer a new paradigm of Islamic Law for theRenewal of Sharia Business Law in Indonesia: A Study of Analysis on theCompilation of Islamic Economic Law. The research method used isqualitative method of literature with content analysis approach. The resultof this research is the importance of changing the paradigm of ideologyinto the paradigm of Islamic law as an institution in sharia business law forIndonesian Muslim society. The paradigm of the institution is extractedfrom Islamic law namely qiyas and maslahah.